Control of Ziegler–Natta catalyst activity by the structural design of alkoxysilane-based external donors. (14th April 2020) - Khatri, Vikas; Sahoo, Usharani; Kaur, Sukhdeep; Rani, Rashmi; Singh, Gurmeet; Kapur, Gurpreet Singh; Kashyap, Hemant K.
Abstract : Herein, the evaluation of four commercial alkoxysilanes and two laboratory synthesized novel diethoxysilacycloalkanes as external donors towards propylene polymerization has been done. Abstract : Herein, the evaluation of four commercial alkoxysilanes and two laboratory synthesized novel diethoxysilacycloalkanes as external donors towards propylene polymerization has been done. Propylene polymerizations were carried out using a fourth generation Ziegler–Natta (ZN) catalyst containing diisobutylphthalate (DIBP) as an internal donor in conjunction with triethylaluminium (TEAL ) as a co-catalyst. The performance of the six external donors studied herein has been described by correlating the experimental results with the predictions from density functional theory calculations. The theoretical binding energies of the complex formed between the external donors and the co-catalyst were found to have a reasonable correlation with the experimentally measured productivity of polypropylene. The comparative results confirmed that certain essential structural characteristics of the external donors are prerequisites to achieve enhanced activity of the catalyst and the stereospecificity of polypropylene.